Characterization of Erwinia gerundensis A4, an Almond-Derived Plant Growth-Promoting Endophyte - Saldierna Guzmán, J. Paola; Reyes-Prieto, Mariana; Hart, Stephen C. (Frontiers in Microbiology, 2021)
The rapidly increasing global population and anthropogenic climate change have created intense pressure on agricultural systems to produce increasingly more food under steadily challenging environmental conditions. Simultaneously, industrial agriculture is negatively affecting natural and agricultural ecosystems due to intensive irrigation and fertilization to fully utilize the potential of high-yielding cultivars. Growth promoting microbes that increase stress tolerance and crop yield could be a useful tool for helping mitigate these problems. We investigated if commercially grown almonds might be a resource for plant colonizing bacteria with growth promotional traits that could be used to foster more productive and sustainable agricultural ecosystems. We isolated an endophytic bacterium from almond leaves that promotes growth of the model plant Arabidopsis thaliana. Genome sequencing revealed a novel Erwinia gerundensis strain (A4) that exhibits the ability to increase access to plant nutrients and to produce the stress mitigating polyamine spermidine. Because Erwinia gerundensis is able to colonize diverse plant species including cereals and fruit trees, A4 may have the potential to be applied to a wide variety of crop systems.